Kicking Ash: Who (or What) is Winning the "War on Coal"?. Issue 7 (21st February 2021) - Drake, David F.; York, Jeffrey G.
Abstract : US coal‐fired generating capacity has shed nearly 25% of its footprint between 2011 and 2018. Multiple factors—regulation, natural gas prices, renewable energy adoption, and environmental activism—have each been lauded by various stakeholders for this trend. To improve our understanding of this environmental technology transition, it is important to determine the extent to which each of these factors has accelerated coal unit retirements. We do so in this study through an accelerated failure time model that utilizes data on US coal‐fired generating units from 2008 through 2016. Our findings indicate that environmental regulation, reduced natural gas price volatility, increased utilization of renewable capacity, and the Sierra Club's Beyond Coal campaign have all accelerated coal unit retirements. We do not, however, find evidence that natural gas price levels or the penetration of renewable capacity have accelerated coal unit retirements. Among the significant drivers, we estimate that the Beyond Coal campaign has had the greatest effect per unit, reducing expected operating life by an average of 24.4 months. However, among these factors, federal regulation affected the greatest number of coal units, and thus had the greatest aggregate impact on coal retirements. In post hoc analysis, we estimate that 40% of the generation that had been provided by retired coal‐fired units spilled over to surviving coal‐fired units. However, we estimate the 60% that was displaced from the coal fleet resulted in a 103.6 to 178.2 million metric ton net reduction in CO 2 emissions each year.